XML-based DEVS modelling and simulation tracking. (21st April 2020) - Dahmani, Youcef; Ali, Hemza Nedjari Benhadj; Boubekeur, Abdelkader
Discrete event system specification (DEVS) is a modelling and simulation formalism for discrete event dynamic systems. DEVS has known different variants and software implementations to meet specific needs. Unfortunately, these implementations do not necessarily share models and cannot capitalise on model reuse and data exchange. XML, as a meta-language, seems to be an appropriate language for helping modellers with weak programming knowledge. Indeed, XML is adopted as a standard for information exchange and knows an increasingly important use on the web. This work aims at determining an XML-based implementation of DEVS for devising an efficient modelling and simulation framework. After defining and validating our XML schemas, an execution step of these models is defined based on our XML abstract simulator which executes a set of XSLT transformations and generates an XML simulation tree describing the different steps of the system during the simulation time.